Urinary mutagenicity and other biomarkers of occupational smoke exposure of wildland firefighters and oxidative stress. (28th January 2019) - Adetona, Anna M.; Kyle Martin, William; Warren, Sarah H.; Hanley, Nancy M.; Adetona, Olorunfemi; Zhang, Junfeng (Jim); Simpson, Christopher; Paulsen, Mike; Rathbun, Stephen; Wang, Jia-Sheng; DeMarini, David; Naeher, Luke P.
Abstract: Background: Wildland firefighters conducting prescribed burns are exposed to a complex mixture of pollutants, requiring an integrated measure of exposure. Objective: We used urinary mutagenicity to assess if systemic exposure to mutagens is higher in firefighters after working at prescribed burns versus after non-burn work days. Other biomarkers of exposure and oxidative stress markers were also measured. Methods: Using a repeated measures study design, we collected urine before, immediately after, and the morning after a work shift on prescribed burn and non-burn work days from 12 healthy subjects, and analyzed for malondialdehyde (MDA), 8-isoprostane, 1-hydroxypyrene (OH-pyrene), and mutagenicity in Salmonella YG1041 +S9. Particulate matter (PM2.5 ) and carbon monoxide (CO) were measured by personal monitoring. Light-absorbing carbon (LAC) of PM2.5 was measured as a surrogate for black carbon exposure. Linear mixed-effect models were used to assess cross-work shift changes in urinary biomarkers. Results: No significant differences occurred in creatinine-adjusted urinary mutagenicity across the work shift between burn days and non-burn days. Firefighters lighting fires had a non-significant, 1.6-fold increase in urinary mutagenicity for burn versus non-burn day exposures. Positive associations were found between cross-work shift changes in creatinine-adjusted urinary mutagenicity and MDA ( p = 0.0010), OH-pyrene ( p = 0.0001), and mass absorption efficiency which is the LAC/PM2.5 ratio ( p = 0.2245), respectively. No significant effect of day type or work task on cross-work shift changes in MDA or 8-isoprostane was observed. Conclusion: Urinary mutagenicity may serve as a suitable measure of occupational smoke exposures among wildland firefighters, especially among those lighting fires for prescribed burns.